GAMBARAN PEMBIAYAAN PRAKTIK KERJA PROGRAM KEAHLIAN TEKNIK KONSTRUKSI KAYU KELAS XII DI SMK NEGERI 2 SIJUNJUNG TAHUN AJARAN 2018/2019 - Nyardi .; Risma Apdeni, ST, MT (Universitas Negeri Padang, 2019)
Abstract— This research was motivated by the absence of real calculations regarding the size of the unit cost of workshop in the building departement . The purpose of this research is to reveal the real unit cost of woodworking practice for each student of Wood Construction Engineering Expertise Program in SMK N 2 Sijunjung based on the job given. The data analysis technique used in this research was quantitative descriptive analysis. The subjects were syllabus/curriculum, teaching materials, and the job sheet of the Wood Construction Engineering Expertise Program at SMK N 2 Sijunjung. Data were gained from observation, direct documentation in the woodworking workshop and direct interviews with deputy of headmaster, head of department, head of workshop and teachers of practical course of Wood Construction Engineering Department in SMK Negeri 2 Sijunjung.Based on the results of data analysis of unit cost, the cost needed for woodworking practice material in class XII is Rp 8.061.000,00 each semester for 23 students. The woodworking practice uses disposable materials (wood) that cannot be recycled or reused, so that new materials must be purchased every year. Keywords: Work Practice Financing, Building Department